Use of the atmospheric generators for capnophilic bacteria Genbag-CO2 for the evaluation of in vitro Plasmodium falciparum susceptibility to standard anti-malarial drugs - Travers Dominique (Malaria Journal, 2011)
Abstract Background The aim of this study was to evaluate the cultivation system in which the proper atmospheric conditions for growing Plasmodium falciparum parasites were maintained in a sealed bag. The Genbag® system associated with the atmospheric generators for capnophilic bacteria Genbag CO2® was used for in vitro susceptibility test of nine standard anti-malarial drugs and compared to standard incubator conditions. Methods The susceptibility of 36 pre-identified parasite strains from a wide panel of countries was assessed for nine standard anti-malarial drugs (chloroquine, quinine, mefloquine, monodesethylamodiaquine, lumefantrine, dihydroartemisinin, atovaquone and pyrimethamine) by the standard 42-hour 3H-hypoxanthine uptake inhibition method using the Genbag CO2® system and compared to controlled incubator conditions (5% CO2 and 10% O2). Results The counts per minute values in the control wells in incubator atmospheric conditions (5% CO2 and 10% O2) were significantly higher than those of Genbag® conditions (2738 cpm vs 2282 cpm, p < 0.0001). The geometric mean IC50 estimated under the incubator atmospheric conditions was significantly lower for atovaquone (1.2 vs 2.1 nM, p = 0.0011) and higher for the quinolines: chloroquine (127 vs 94 nM, p < 0.0001), quinine (580 vs 439 nM, p < 0.0001), monodesethylamodiaquine (41.4 vs 31.8 nM, p < 0.0001), mefloquine (57.5 vs 49.7 nM, p = 0.0011) and lumefantrine (23.8 vs 21.2 nM, p = 0.0044). There was no significant difference of IC50 between the 2 conditions for dihydroartemisinin, doxycycline and pyrimethamine. To reduce this difference in term of anti-malarial susceptibility, a specific cut-off was estimated for each drug under Genbag® conditions by regression. The cut-off was estimated at 77 nM for chloroquine (vs 100 nM in 10% O2), 611 nM for quinine (vs 800 nM), 30 nM for mefloquine (vs 30 nM), 61 nM for monodesethylamodiaquine (vs 80 nM) and 1729 nM for pyrimethamine (vs 2000 nM). Conclusions The atmospheric generators for capnophilic bacteria Genbag CO2® is an appropriate technology that can be transferred to the field for epidemiological surveys of drug-resistant malaria. The present data suggest the importance of the gas mixture on in vitro microtest results for anti-malarial drugs and the importance of determining the microtest conditions before comparing and analysing the data from different laboratories and concluding on malaria resistance.